Evolutionary Analysis of Snf1-Related Protein Kinase2 (SnRK2) and Calcium Sensor (SCS) Gene Lineages, and Dimerization of Rice Homologs, Suggest Deep Biochemical Conservation across Angiosperms - Holappa, Lynn D.; Ronald, Pamela C.; Kramer, Elena M. (Frontiers in Plant Science, 2017)
Members of the sucrose non-fermenting related kinase Group2 (SnRK2) subclasses are implicated in both direct and indirect abscisic acid (ABA) response pathways. We have used phylogenetic, biochemical, and transient in vivo approaches to examine interactions between Triticum tauschii protein kinase (TtPK1) and an interacting protein, Oryza sativa SnRK2-calcium sensor (OsSCS1). Given that TtPK1 has 100% identity with its rice ortholog, osmotic stress/abscisic acid-activated protein kinase (OsSAPK2), we hypothesized that the SCS and TtPK1 interactions are present in both wheat and rice. Here, we show that SnRK2s are clearly divided into four pan-angiosperm clades with those in the traditionally defined Subclass II encompassing two distinct clades (OsSAPK1/2 and OsSAPK3), although OsSAPK3 lacks an Arabidopsis ortholog. We also show that SCSs are distinct from a second lineage, that we term SCSsister, and while both clades pre-date land plants, the SCSsister clade lacks Poales representatives. Our Y2H assays revealed that the removal of the OsSCS1 C-terminal region along with its N-terminal EF-hand abolished its interaction with the kinase. Using transient in planta bimolecular fluorescence complementation experiments, we demonstrate that TtPK1/OsSCS1 dimerization co-localizes with DAPI-stained nuclei and with FM4-64-stained membranes. Finally, OsSCS1- and OsSAPK2-hybridizing transcripts co-accumulate in shoots/coleoptile of drying seedlings, consistent with up-regulated kinase transcripts of PKABA1 and TtPK1. Our studies suggest that interactions between homologs of the SnRK2 and SCS lineages are broadly conserved across angiosperms and offer new directions for investigations of related proteins.